Legal Protection For Heirs Of Land Deeds That Only Use The Name Of Their First Child In The Perspective Of Islamic Inheritance Law And Civil Law - nastopa, fitriyan ferdi (International Significance of Notary, 2022)
There are different classifications of heirs which make up the inheritance distribution system in Indonesia, because in Indonesia the law of inheritance is divided into 3 (three), namely: the civil inheritance law system, the inheritance law system and Islamic law. Due to the layman's law, there are many legal actions where one of the parents made the land deed using the name of his first child without using the names of other heirs. So that many disputes occur when their parents die, because the child who is recorded on the land deed thinks that it belongs to him absolutely, so I researched Legal Protection for Heirs of Land Deeds That Only Use the Name of their First Child in the Perspective of Islamic Inheritance Law and Civil Law. So that there are two formulations of the problem. 1 (one) What is the status of the heirs' rights to the land deed that only uses the name of their first child? 2 (Two) How is the legal protection of heirs for land deeds that only use the name of their first child from the perspective of Islamic inheritance law and civil law?The type of research used is normative juridical, namely research that refers to legal norms contained in statutory regulations. The nature of the research is analytical descriptive through a statute approach. The results of this study, the status of heirs' rights to land deeds that only use the name of their first child is that in principle all heirs are entitled to an equal share of inheritance, regardless of gender. So even though the land deed only uses the name of the first child, the other heirs are still entitled to receive the inheritance from the heir. Because Article 852 of the Civil Code has determined that the first people who according to law are entitled to receive an inheritance are children and the husband or wife lives the longest. The portion they receive is also equal to one another. There is no difference between men and women, and there is also no difference between the first born and the next born. There are two legal protections for heirs against land deeds that only use the name of their first child, the first is preventive, a form of prevention from assets left by heirs in the form of land deeds using only the name of their first child is in the form of good faith among heirs. in the implementation of the application for determination of heirs, on the one hand to seek justice, on the other hand, to determine who is the heir, to determine the inheritance, to determine the share of each heir, and to carry out the distribution of the inheritance. the second is repressive legal protection aimed at resolving disputes. In this study, the cancellation of the deed, with the aim that when there is a dispute or physical possession of property controlled by one of the heirs on the pretext that he has a deed given by his parents on his behalf, then the deed must be canceled, with the aim that the other heirs do not someone is harmed.Keywords: Legal Protection, Land Deed, Inheritance